2003
DOI: 10.1021/ol035106o
|View full text |Cite
|
Sign up to set email alerts
|

First Examples of Improved Catalytic Asymmetric C−C Bond Formation Using the Monodentate Ligand Combination Approach

Abstract: Using a combination of chiral monodentate phosphoramidite ligands in the rhodium-catalyzed conjugate addition of boronic acids to three different substrates, we have shown for the first time that the ligand combination approach is applicable for C−C bond formation. Chiral catalysts based on hetero-combinations of ligands are found to be more effective than the homo-combinations. 31 P NMR experiments show that the hetero-combinations are formed in excess over the homo-combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(47 citation statements)
references
References 24 publications
(21 reference statements)
0
43
0
4
Order By: Relevance
“…[220] In the case of a simple ML 2 model with a mixture of two different enantiopure monodentate ligands, L x and L y , three types of catalysts, Classical nonlinear effects can be considered to result from a library of complexes built from two enantiomeric ligands (ML 2 , ML 3 , ML 4 etc). The use of a mixture of different ligands creates a more complicated library of complexes, which can give rise to interesting nonlinear effects.…”
Section: Mixtures Of Nondiastereomeric Chiral Complexesmentioning
confidence: 99%
“…[220] In the case of a simple ML 2 model with a mixture of two different enantiopure monodentate ligands, L x and L y , three types of catalysts, Classical nonlinear effects can be considered to result from a library of complexes built from two enantiomeric ligands (ML 2 , ML 3 , ML 4 etc). The use of a mixture of different ligands creates a more complicated library of complexes, which can give rise to interesting nonlinear effects.…”
Section: Mixtures Of Nondiastereomeric Chiral Complexesmentioning
confidence: 99%
“…Bei Verwendung von nur einem chiralen Liganden tritt oft auch der gegenteilige Effekt auf. [102,103] Mit Gemischen verschiedener chiraler einzähniger Phosphonite L13-L14 konnten bei der Rh-katalysierten Hydrierung der substituierten Alkene 14 bessere Enantioselektivitäten erzielt werden als mit nur einem chiralen Liganden (Schema 4). [94,100] Der gleiche Ansatz wurde auch auf andere Umsetzungen angewendet, beispielsweise die C-C-Verknüpfung (siehe unten).…”
Section: Phosphoramidite: Struktur Synthese Und Eigenschaftenunclassified
“…In particular, excellent results were achieved in the addition to a,b-unsaturated carbonyl compounds. [3] However, despite the great synthetic importance of nitro compounds, [4] it is surprising that far fewer studies reported the efficient asymmetric addition of boronic acids to nitroalkenes, most likely because of the difficulty in controlling the reaction stereoselectivity.[5] In fact, high enantioselectivities were only achieved by the Hayashi group in the asymmetric addition of organoboronic acids to a-substituted 1-nitroalkenes using a rhodium/binap (binap = 2,2-bis(diphenylphosphanyl)-1,1 -binaphthyl) catalyst.[6] In other reports, [7] low levels of enantiomeric enrichment (< 50 % ee) were often observed with general 1-nitroalkene substrates that lack a substitutents. Therefore, the development of a capable catalyst system for efficient asymmetric boronic acid addition to nitroalkenes is highly desirable.…”
mentioning
confidence: 99%